Centrum Canis - Kovářová, Lucie (Vysoké učení technické v Brně. Fakulta stavební, 2025)
Předmětem diplomové práce je projektová dokumentace stavby Centra Canis. Stavba se nachází na ulici Tumaňanova v Brně - Mokrá Hora. Jedná se o solitérní objekt se dvěma nadzemními a jedním podzemním podlažím. Objekt se dělí na více částí, a to na veterinární ordinaci, obchod, myčku pro psy, část školícího centra a administrativní část. Všechny části objektu jsou přístupné z parkoviště před objektem. Hlavními nosnými prvky stavby jsou zděné vertikální konstrukce z cihelných tvárnic typu therm ztužené železobetonovými věnci, monolitické železobetonové stropní desky a montované stropy s nosníky a keramickými vložkami. Schodiště jsou železobetonová s přilehlou šachtou s výtahem. Objekt je založen na pasech z prostého betonu, které jsou odstupňované do úrovně suterénu. Objekt je zateplen kontaktním zateplovacím systémem ETICS z čedičové minerální vlny. Budova je posouzena z hlediska stavební fyziky, a to tepelně technických požadavků, akustiky, denního osvětlení. Fasáda hlavní hmoty je obložena pohledovým plechem s pilovitým tvarem s provětráváním a v ostatních částech použita fasádní omítka. Objekt je navržen s vegetační střechou.

The subject of the thesis is the project documentation for the construction of the Canis Center. The building is located on Tumaňanova Street in Brno - Mokrá Hora. It is a standalone structure with two above-ground floors and one underground floor. The building is divided into several sections, including a veterinary clinic, a shop, a dog washing station, a training center section, and an administrative area. All parts of the building are accessible from the parking lot in front of the building. The main load-bearing elements of the building consist of vertical masonry structures made of therm-type brick blocks, reinforced with reinforced concrete beams, monolithic reinforced concrete ceiling slabs, and prefabricated ceilings with beams and ceramic inserts. The stairs are made of reinforced concrete, adjacent to a shaft housing an elevator. The building is founded on stepped plain concrete footings that extend to the basement level. It is insulated with an ETICS contact insulation system made of basalt mineral wool. The building is evaluated in terms of building physics, including thermal performance, acoustics, and natural daylighting. The facade of the main mass features exposed sheet metal with a sawtooth pattern and ventilation, while other areas are finished with facade plaster. The building is designed with a green roof.
Canis Center
Keywords: Centrum Canis; multifunkční objekt; novostavba; keramické tvárnice; plochá vegetační střecha; Canis Center; a multifunctional building; new construction; ceramic blocks; flat green roof